PEMAHAMAN HADITS SECARA TEKSTUAL DAN KONTEKSTUAL - Abdul Ropi Amrullah (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Hadith is the words and deeds of the Prophet Muhammad SAW which is also the second source of Islamic law for Muslims. However, in understanding the hadith there are many differences contained in it. One of them is the discussion of the hadith textually and contextually. The purpose of this study is to find out and understand how to understand the hadith textually and contextually. By using the library search research method. The results of this study are that the textual approach in the hadith is to understand the meaning and intent contained in the hadiths of the Prophet SAW. In relying on the analysis of the hadith text. In other words, understanding the hadith is only in accordance with the text without looking at the others. As for understanding the hadith contextually, namely the explanation or information that accommodates the clarity of meaning, besides that contextual means a condition that is closely related to the events that occur throughout the space and time that surrounds it.